Penerapan Media “Teleng” Untuk Meningkatkan Hasil Belajar Sistem Gerak Manusia - Teguh Soeharto (Jurnal Lingkar Mutu Pendidikan, 2021)
Minimum completeness criteria for the movement system in humans at SMP Negeri 3 Babelan in 2020 shows learning outcomes. It was caused by the limited media that can be used to learn concepts. Media "Teleng" (tepung lengket) requires students to study the concept in depth, which is a background for conducting this research. The objectives of this study are: (1) to elaborate the learning outcome improvement; (2) to explain the teaching and learning process; and (3) to explain student responses. Teleng is a medium in the form of bones from clay with lots of advantages such as, easy to hand-made, easily-obtained materials, and durable. This study used the R & D method, with a 4D model. The data were obtained through observation of the learning process, and responses, as well as evaluation of learning outcomes. The research instrument uses learning outcomes test, observation of learning activities and responses. The conclusions are: (1) learning outcomes of the human locomotory system can be improved; (2) Teleng is practically used in the learning process; and (3) Teleng attracts students' attention. The results of this learning innovation media research can be used as an alternative to improve learning outcomes for the concept of the human locomotory system